Preseptal Cellulitis Versus Orbital Cellulitis: A Pediatric Case. (July 2022) - Milo, Razel B.
Abstract : Eye infection with or without swelling is a common complaint in pediatric patients. It commonly affects the eyelid, which can be confused with an insect bite, orbital pseudotumor, or panophthalmitis. The article highlights the differences between preseptal and orbital cellulitis. Preseptal and orbital cellulitis originate from other infections because of the thin bone barrier that separates the eye from other facial structures. The clinical manifestations of preseptal and orbital cellulitis may be perplexing, and emergency nurse practitioners must distinguish between the two infections. The incorrect diagnosis may lead to complications. The complications associated with orbital cellulitis are vision loss, brain abscess, vision loss, cavernous sinus thrombophlebitis, orbital cellulitis, subperiosteal abscess, and death. Thus, early diagnosis and treatment will prevent these complications.